Key principles of drug therapy in patients with chronic myeloid leukemia - A. V. Zhuravlev; O. I. Knysh (IRBIS LLC, 2023)
Objective: to summarize scientific information about the basic principles of modern drug therapy for patients with chronic myeloid leukemia (CML) considering their individual characteristics.Material and methods. The basis of the study included modern scientific articles and clinical guidelines on CML diagnosis and treatment (2021), State Register of Medicines (SRM) of the Russian Federation, instructions for the use of medicines. The following methods were used: structural analysis, analytical method, content analysis, retrospective analysis, systematic approach, situational-logical and graphical methods of analysis.Results. The analysis made it possible to summarize scientific information about the basic principles of drug therapy for patients suffering from CML. It was revealed that the problem of CML therapy today is relevant, since every year there is an increase in the incidence of this nosology. Currently, the most significant is the prescription of tyrosine kinase inhibitors (TKIs), since they have pronounced effects and are well tolerated by patients. Therapy for CML in TKIs prescription consists of several lines. Imatinib is the first line therapy because it has better safety profile. There are combinations with imatinib; for example, it is used together with interferon alfa, which allows, in some cases, to increase the response to treatment. The following drugs are used in the second line: nilotinib, dasatinib, bosutinib, ponatinib. If TKI therapy is ineffective, it is possible to prescribe standard chemotherapy, interferon therapy, or bone marrow transplantation in the absence of contraindications. Studies are underway on the possibility of using and including in clinical guidelines such drugs as arsenic trioxide, decitabine, omacetaxime, inhibitors of farnesyl transferases, granulocyte-macrophage factors, antitumor vaccines. The analysis of SRM identified 27 trade names for TKIs, the share of domestic drugs was 60%. There were no Russian analogues for bosutinib and ponatinib in SRM, which are recommended for use in case of ineffective TKI therapy of previous lines.Conclusion. The study of drug provision for CML patients is an urgent task for pharmaceutical practice and for the healthcare system as a whole. Currently, the acute issues are the individual approach to the treatment of each CML patient considering concomitant diseases, and the search for new, more effective drugs that can increase the life expectancy and quality of life of patients suffering from this disease.